Overview on the Role of E-Cadherin in Gastric Cancer: Dysregulation and Clinical Implications - Zhao, Huichen; Hu, Huihui; Chen, Beibei; Xu, Weifeng; Zhao, Jing; Huang, Chen; Xing, Yishu; Lv, Huifang; Nie, Caiyun; Wang, Jianzheng; He, Yunduan; Wang, Sai-Qi; et al. (Frontiers in Molecular Biosciences, 2021)
Gastric cancer is the fifth most common cancer and the third most common cause of cancer death all over the world. E-cadherin encoded by human CDH1 gene plays important roles in tumorigenesis as well as in tumor progression, invasion and metastasis. Full-length E-cadhrin tethered on the cell membrane mainly mediates adherens junctions between cells and is involved in maintaining the normal structure of epithelial tissues. After proteolysis, the extracellular fragment of the full-length E-cadhein is released into the extracellular environment and the blood, which is called soluble E-cadherin (sE-cadherin). sE-cadherin promots invasion and metastasis as a paracrine/autocrine signaling molecule in the progression of various types of cancer including gastric cancer. This review mainly summarizes the dysregulation of E-cadherin and the regulatory roles in the progression, invasion, metastasis, and drug-resistance, as well as its clinical applications in diagnosis, prognosis, and therapeutics of gastric cancer.